Women's MSMEs Go Digital: Training and Implementation E-commerce in Balaraja District - Hamdani, Hamdani; Suharti, Eni; Suryadi, Suryadi; Sukesih, Sukesih; Santoso, Yudi; Aproji, Alan; Fadilah, Suci; Nurazizah, Dinda Suci; Abinaya, Afdal; Fadilah, Selvia (EQUATOR SINAR AKADEMIA, 2025)
This Community Service Activity (PKM) aims to increase the capacity of female MSME actors in Balaraja District in the use of digital technology, especially e-commerce. This program began with the construction of a local e-commerce platform called Bala Niaga, which is designed as a digital marketing tool that is easily accessible to local MSMEs. Furthermore, face-to-face training was carried out which included an understanding of digital business concepts, online marketing strategies, and hands-on practice of using the platform. The training was attended by 55 female MSME participants assisted by the Tangerang Regency Cooperatives and SMEs Office. The results of the observation showed an increase in participants' understanding of e-commerce, and as many as 84% of participants successfully registered and activated online stores in Bala Niaga. This activity shows that the combination of digital platform development and applied training is effective in encouraging the digital transformation of women's MSMEs. Continuous assistance is needed so that the use of this technology can be more optimal and sustainable.